Navigating dual logics: A framework for integrating financial performance and social impacts in Indonesian village-owned enterprises (BUMDES) - Fitriani, Desti (International Journal of Innovative Research and Scientific Studies, 2025)
This study investigates performance measurement challenges in hybrid organizations, focusing on Village-Owned Enterprises (BUMDES) in Indonesia. As hybrid entities, BUMDES balance dual objectives: achieving financial sustainability and delivering social impact. However, tensions arise from resource allocation constraints and diverse stakeholder expectations. The research aims to develop an integrated framework that evaluates economic, social, and environmental outcomes comprehensively. Using qualitative methods, including focus group discussions, direct observations, and document analysis, the study examines 20 BUMDES across West Java and West Nusa Tenggara provinces. Findings reveal the inherent complexity of reconciling profit-oriented and community-focused goals, particularly when resource limitations and a lack of standardized metrics exist. Stakeholders express the need for multidimensional indicators encompassing profitability, job creation, community welfare, and environmental contributions. Proposed strategies, such as segregating revenue streams and fostering participatory governance, align stakeholder priorities and reduce conflicts. This study contributes to hybrid organizational theory by offering actionable insights and a performance framework tailored to BUMDES’ dual missions. It highlights implications for policymakers and practitioners seeking to support hybrid organizations in addressing socio-economic challenges sustainably.